Analysis of harmony between color and fragrance in lighting environments by the reaction of the orbitofrontal area. (June 2022) - Yamashita, Gaku; Tanaka, Midori; Horiuchi, Takahiko
This study focuses on the analysis of the cross-modal effects between sight (color) and smell (fragrance). While most previous researches have studied the harmony of color and fragrance using small-field colors such as patches and display stimuli, this study analyzes harmony in lighting environments. In our experiments, we focused on the finding that emotional states manifest themselves in responses in the orbitofrontal cortex and used near-infrared spectroscopy to evaluate orbitofrontal responses. Five different aromas were prepared for fragmentation. Initially, the observers were asked to select the most pleasant and least unpleasant aromas. The two selected aromas were soaked in non-fat cotton cloth and placed in a light-shielding brown bottle, which was used as a scent stimulus. For the lighting environment, 36 different lighting colors were designed using a luminaire consisting of 14 LEDs. The results of the experiment showed that the lighting color that the observers judged to be harmonious by actually smelling the fragrance (sensory color) activated the orbitofrontal cortex more than the lighting color that they judged to be harmonious by recalling the name of the fragrance (imagery color).